Multidisciplinary student synergy through the KKM program as an effort to improve the quality of health, education, and community environmental awareness - Asep Yudianto; Laila Munawaroh (Community Service for Sustainable Community Journal, 2026)
Background: Student Community Service Program (Kuliah Kerja Mahasiswa-KKM) bridges universities with rural community needs in health, education, environmental management, and social development. Although participatory community service has been shown to improve public knowledge and behavior, evidence on integrated multidisciplinary KKM remains limited. This study analyzed the implementation of a multidisciplinary KKM program in Jayamekar Village from January to February 2026. Methods: A community-based participatory approach was implemented through free health screening, anti-bullying education, biopore training, pest and plant disease counseling, and road reflector installation, supported by school teaching, Qur'an teaching, handwashing campaigns, group exercise, educational competitions, and community events. Data were collected through participatory observation and activity documentation and analyzed descriptively. Findings: 38 residents participated in free health screening and demonstrated increased awareness of early disease detection and healthy lifestyles. More than 70 children showed improved learning motivation, literacy engagement, and understanding of positive social behavior. Environmental activities strengthened community knowledge of organic waste management, while road reflector installation enhanced perceived road safety. The integrated implementation also promoted active community participation and collaboration between university students and local residents. Conclusion: The multidisciplinary KKM program contributed to community empowerment by addressing interconnected health, education, environmental, and social issues through participatory engagement. However, the findings are limited by the descriptive design, single-village setting, and absence of quantitative outcome measures. Novelty/Originality of this article: This study provides empirical evidence on an integrated multidisciplinary KKM model that coordinates health, education, environmental, safety, and social empowerment initiatives within a participatory village-based community service program.